Му-Му. Бездна Кавказа : [роман] / Андрей Воронин - Воронин Андрей Николаевич (Харвест, 2010)
Экземпляры: ф.22 (20181030) / Инвентарный номер: 58769 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 75 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44